1999
DOI: 10.1142/s0218127499001061
|View full text |Cite
|
Sign up to set email alerts
|

Hairs for the Complex Exponential Family

Abstract: In this paper we consider both the dynamical and parameter planes for the complex exponential family E λ (z) = λe z where the parameter λ is complex. We show that there are infinitely many curves or "hairs" in the dynamical plane that contain points whose orbits under E λ tend to infinity and hence are in the Julia set. We also show that there are similar hairs in the λ-plane. In this case, the hairs contain λ-values for which the orbit of 0 tends to infinity under the corresponding exponential. In this case i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 16 publications
2
60
0
1
Order By: Relevance
“…All orbits on this curve (except possibly that of the endpoint) tend to ∞ in the right half plane [6]. This phenomenon occurs for all exponentials [2].…”
Section: Introductionmentioning
confidence: 78%
“…All orbits on this curve (except possibly that of the endpoint) tend to ∞ in the right half plane [6]. This phenomenon occurs for all exponentials [2].…”
Section: Introductionmentioning
confidence: 78%
“…Some of the early prime works dealt mainly with complex exponential family E λ (z) = λe z , [12], [11], [7], [22], while some generalizations to other entire transcendental maps were also found in [12] and more recently in [3], [20]. Among several other topological results, it has been shown that under certain assumptions, the Julia set of an entire transcendental map consists, succinctly, by a Cantor set of curves extending to infinity in a specific asymptotic direction, each one of them having a distinguished landing point, called the endpoint.…”
Section: Julia Sets Of Hyperbolic Transcendental Entire Mapsmentioning
confidence: 99%
“…Dynamic rays have been first introduced by Devaney and Krych in [4] (with the name hairs) and studied for example in [3]. A full classification of the set of escaping points in terms of dynamic rays has been then completed by Schleicher and Zimmer in [19].…”
Section: Dynamic Rays In the Exponential Familymentioning
confidence: 99%